2020
DOI: 10.3390/tropicalmed6010006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational COVID-19 Prevention among Congolese Healthcare Workers: Knowledge, Practices, PPE Compliance, and Safety Imperatives

Abstract: The SARS-CoV-2 (COVID-19) pandemic has had a tremendous impact on the functionality of health systems and world affairs. We assessed knowledge, attitudes, and practices (KAPs) of healthcare workers (HCWs) in the Democratic Republic of the Congo (DRC). This was a cross-sectional study conducted in 23 referral hospitals located in three towns of the DRC (Lubumbashi, Kamina, Mbuji-Mayi). In total, 613 HCWs were surveyed using the World Health Organization’s (WHO’s) “Exposure Risk Assessment in the Context of COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 23 publications
4
27
2
Order By: Relevance
“…In one study, 77% of French healthcare workers reported that they wanted to get vaccinated for COVID-while the willingness to get vaccinated was 28% among healthcare workers in Kongo. 8 In a study on the potential acceptance of the COVID-19 vaccine in June 2020, among 13 426 people randomly selected from 19 countries, mainly with a high COVID-19 burden, 72% of the participants reported they would accept vaccination if the vaccine proved safe and effective. 9 As demonstrated by various studies, the context in which these studies are developed are highly dynamic and changing, with daily variations in perceived disease threat and COVID-19 vaccine development itself, and thus variances in results of surveys are seen at different periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 77% of French healthcare workers reported that they wanted to get vaccinated for COVID-while the willingness to get vaccinated was 28% among healthcare workers in Kongo. 8 In a study on the potential acceptance of the COVID-19 vaccine in June 2020, among 13 426 people randomly selected from 19 countries, mainly with a high COVID-19 burden, 72% of the participants reported they would accept vaccination if the vaccine proved safe and effective. 9 As demonstrated by various studies, the context in which these studies are developed are highly dynamic and changing, with daily variations in perceived disease threat and COVID-19 vaccine development itself, and thus variances in results of surveys are seen at different periods.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of willingness among HCPs may differ from country to country. In one study, 77% of French healthcare workers reported that they wanted to get vaccinated for COVID‐19 7 while the willingness to get vaccinated was 28% among healthcare workers in Kongo 8 . In a study on the potential acceptance of the COVID‐19 vaccine in June 2020, among 13 426 people randomly selected from 19 countries, mainly with a high COVID‐19 burden, 72% of the participants reported they would accept vaccination if the vaccine proved safe and effective 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, researchers observed the compliance rate of HCWs to proper PPE use -in a special unit for suspected and confirmed COVID-19 cases-and found it to be 31.5% [ 21 ]. Also, low rate of consistent PPE use was reported in Congo [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in the Congo, Michel-Kabamba et al Assessed the performance of health care workers toward preventive measures against Covid-19 as poor, which is inconsistent with the present study. 19 also, Arnetz et al 20 conducted a study to investigate the use of PPE in nurses during the COVID-19 pandemic. They assessed the performance of nurses at a moderate level, which is not consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%